DPPA3-HIF1α axis controls colorectal cancer chemoresistance by imposing a slow cell-cycle phenotype - Estefania Cuesta-Borràs; Cándida Salvans; Oriol Arqués; Irene Chicote; Lorena Ramírez; Laia Cabellos; Jordi Martínez-Quintanilla; Alex Mur-Espinosa; Alejandro García-Álvarez; Jorge Hernando; Juan Ramón Tejedor; Oriol Mirallas; et al. (Cell Reports, 2023)
Summary: Tumor relapse is linked to rapid chemoresistance and represents a bottleneck for cancer therapy success. Engagement of a reduced proliferation state is a non-mutational mechanism exploited by cancer cells to bypass therapy-induced cell death. Through combining functional pulse-chase experiments in engineered cells and transcriptomic analyses, we identify DPPA3 as a master regulator of slow-cycling and chemoresistant phenotype in colorectal cancer (CRC). We find a vicious DPPA3-HIF1α feedback loop that downregulates FOXM1 expression via DNA methylation, thereby delaying cell-cycle progression. Moreover, downregulation of HIF1α partially restores a chemosensitive proliferative phenotype in DPPA3-overexpressing cancer cells. In cohorts of CRC patient samples, DPPA3 overexpression acts as a predictive biomarker of chemotherapeutic resistance that subsequently requires reduction in its expression to allow metastatic outgrowth. Our work demonstrates that slow-cycling cancer cells exploit a DPPA3/HIF1α axis to support tumor persistence under therapeutic stress and provides insights on the molecular regulation of disease progression.